IPTEKS SISTEM INFORMASI AKUNTANSI PENJUALAN KREDIT LEASING PADA PT. HASJRAT ABADI CABANG TENDEAN MANADO - Usoh, Ayudia Claudia; Lengkong, Sesca Angelita; Mintalangi, Syermi S.E. (Universitas Sam Ratulangi, 2018)
The economic condition of a country will effect people’s society lifestyle, as matter of fact what happen in Indonesia especially Manado City. At this point in time the lifestyles improvement of people society in Manado City make needs of transportation in this topic as a cars grow up faster. Therefore many company as dealer having a high competition in market, so they need to win customer’s heart to sell their product. Every company have their own strategy, so that PT. Hasjrat Abadi Tendean do credit selling for their costumer as their strategy. By means of working together with the best Leasing partner they can have the ability in order to sell as many cars by credit as they can and can improve their sales volume and also to improve their profit.Keywords: Credit, Leasing, Sales System, Profit, Sales Volume